The multifaceted structure of nursing: an Aristotelian analysis - Whelton, Beverly J. B. (Nursing philosophy, 2002)
A careful reading of Aristotle's Nicomachean Ethics focusing on his treatment of politics reveals a multifaceted discipline with political science, legislation, practice and ethics. These aspects of the discipline bear clear resemblance to the multiple conceptions of nursing. The potential that nursing is a multifaceted discipline, with nursing science as just one facet challenges the author's own conception of nursing as a practical science. Aristotle's discussion would seem to argue that nursing science is nursing, but nursing is more. Nursing is also ethical practice, or art, and legislative for health. The multifaceted discipline of politics is united by the end, the common good, a just community that makes human happiness possible. Reasoning in this way, nursing is unified by its end, health of individuals and communities. Since nursing is not unique in having health as its end, this discussion ends with the question of where its uniqueness lies, i.e. within the activities or the personal presence of its practitioners. This discussion also contains some of the contemporary ethical and legislative challenges with which nursing is confronted.